Community health workers and health equity in low- and middle-income countries: systematic review and recommendations for policy and practice - Sonia Ahmed; Liana E. Chase; Janelle Wagnild; Nasima Akhter; Scarlett Sturridge; Andrew Clarke; Pari Chowdhary; Diana Mukami; Adetayo Kasim; Kate Hampshire (International Journal for Equity in Health, 2022)
Abstract Background The deployment of Community Health Workers (CHWs) is widely promoted as a strategy for reducing health inequities in low- and middle-income countries (LMIC). Yet there is limited evidence on whether and how CHW programmes achieve this. This systematic review aimed to synthesise research findings on the following questions: (1) How effective are CHW interventions at reaching the most disadvantaged groups in LMIC contexts? and (2) What evidence exists on whether and how these programmes reduce health inequities in the populations they serve? Methods We searched six academic databases for recent (2014–2020) studies reporting on CHW programme access, utilisation, quality, and effects on health outcomes/behaviours in relation to potential stratifiers of health opportunities and outcomes (e.g., gender, socioeconomic status, place of residence). Quantitative data were extracted, tabulated, and subjected to meta-analysis where appropriate. Qualitative findings were synthesised using thematic analysis. Results One hundred sixty-seven studies met the search criteria, reporting on CHW interventions in 33 LMIC. Quantitative synthesis showed that CHW programmes successfully reach many (although not all) marginalized groups, but that health inequalities often persist in the populations they serve. Qualitative findings suggest that disadvantaged groups experienced barriers to taking up CHW health advice and referrals and point to a range of strategies for improving the reach and impact of CHW programmes in these groups. Ensuring fair working conditions for CHWs and expanding opportunities for advocacy were also revealed as being important for bridging health equity gaps. Conclusion In order to optimise the equity impacts of CHW programmes, we need to move beyond seeing CHWs as a temporary sticking plaster, and instead build meaningful partnerships between CHWs, communities and policy-makers to confront and address the underlying structures of inequity. Trial registration PROSPERO registration number CRD42020177333 .